A feasibility study on CoaPe fuel pellets from municipal solid wastes - Gonzales, Genalin; Javillo, Marie Chris; Miranda, Maria Moselle Lara; Sumaljag, Mark Anthony V. (Quezon City College of Engineering, University of the Philippines Diliman, 2012)
The study aims to assess the feasibility of CoaPe, a torrefied fuel pellet made from solid municipal wastes. It undergoes the process of torrefaction to achieve high quality process. It is currently being marketed as an eco-friendly and affordable substitute for coal. For the first stage of the study, the key features of the product are established. From this, the product's main and indirect competitors were determined. Product Strengths were used to further build up the product's advantage compared to its competitors. This led to the identification of the potential customers and market shares. Several marketing and sales strategies were also planned to attract these potential customers, which includes giving the potential customers a demo and sample CoaPe. For the initial year, a marketing budget of Php 1.8 million was identified. Furthermore, approximately, Php 80 million tn revenues is expected for the first two years. It ts expected that this will increase to Php 90 million for the succeeding years due to the increase in efficiency of the design capacity. For the next stage, projected demand for the product was used to determine the required amount of CoaPe to be produced. As such, the minimum operating requirements were set up. This includes the identification and of the required number of machines and equipment to be used and the elimination of possible sites for the plant site. Key people for the start-up of the organization were also assigned. Based from the available data, a cost analysis was made to verify whether the project is still within the given budget. As a conclusion to the technical study, an initial project cost of Php 70 million is identified. After identifying the necessary project costs to set up the business, it was planned how to source the required funds. It was determined that Php 40 million of funds will be needed. Php 10 million will be from loans, Php 20 million from investors, and Php 10 million from the owner. Financial statements were then prepared to determine the feasibility of operating the business, and analyses made from these financial statements showed that the business is indeed profitable. After the financial study, it is determined that the operation is financially feasible. Finally. based from the social profitability study. the project is a socially beneficial venture. Overall, this project is feasible in an aspects.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Wood pellets; Feasibility studies